Proceedings of the 2004 ACM Workshop on Rapid Malcode 2004
DOI: 10.1145/1029618.1029627
|View full text |Cite
|
Sign up to set email alerts
|

Toward understanding distributed blackhole placement

Abstract: The monitoring of unused Internet address space has been shown to be an effective method for characterizing Internet threats including Internet worms and DDOS attacks. Because there are no legitimate hosts in an unused address block, traffic must be the result of misconfiguration, backscatter from spoofed source addresses, or scanning from worms and other probing. This paper extends previous work characterizing traffic seen at specific unused address blocks by examining differences observed between these block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 11 publications
2
40
0
Order By: Relevance
“…So there are high chances for collecting large amounts of information, as all actions can be logged and analyzed. Any error in the system may allow a hacker to control the full operating system, attack other systems, or intercept messages in the application system [14].…”
Section: E High-interaction Honeypotsmentioning
confidence: 99%
“…So there are high chances for collecting large amounts of information, as all actions can be logged and analyzed. Any error in the system may allow a hacker to control the full operating system, attack other systems, or intercept messages in the application system [14].…”
Section: E High-interaction Honeypotsmentioning
confidence: 99%
“…The SGNET deployment aims at monitoring small sets of IPs deployed in multiple locations of the IP space, in order to characterize the heterogeneity of the activities along the Internet as observed in [14,9]. SGNET sensors are thus low-end hosts meant to be deployed at low cost by different organizations and bound to a limited number of IPs.…”
Section: Sgnet and The Epsilon-gamma-pi-mu Modelmentioning
confidence: 99%
“…An extremely valid instrument to collect information is the honeypot technology. The deployment of honeypots in several locations of the IP space has underlined the fact that different blocks of addresses are attacked differently [14,9]. It is thus extremely important to have in-depth information about these threats in order to study the feasibility of characterizing the different observed segments of the Internet.…”
Section: Introductionmentioning
confidence: 99%
“…Preventive mechanisms by identification of the activities and infiltration of the botnets to stop their operations, are proposed. In [16], an overview of the origins and structure of botnets is presented. It used data from the Internet Motion Sensor project [17] and Honeypot [18] to demonstrate the dangers of botnets due to their increase in number and their ability to exploit common system vulnerabilities such as the DCOM RPC [19] and LSASS [20].…”
Section: Related Workmentioning
confidence: 99%